Open government : fostering dialogue with civil society. (OECD, 2003)
Building open government is a challenge shared by all countries. Transparency and accountability in public administration are enhanced by strong public scrutiny based on solid legal provisions for access to information. Investing in consultation and public participation allows governments to tap new sources of policy-relevant ideas, information and resources when making decisions. These efforts, in turn, contribute to building public trust in government, meeting the expectations of civil society, and strengthening civic capacity.